Helminthological estimation of pastures concerning Protostrongylus spp. in sheep in the mountain zone of Chechen Republic - H. H. Gadaev (Российский паразитологический журнал, 2016)
In Chechen Republic the helminthological estimation of pastures concerning Protostrongylus spp. of sheep are made. Infections of lambs register since June–July. Young growth and adults’ sheep are infected by Protostrongylidae within all the year.